A Community Participatory Oral Health Promotion Program - Maria Rosa Watson, DDS, MS, MPH; Alice M. Horowitz, PhD; Isabel Garcia, DDS, MPH; (2000)
This paper reports the planning, implementation, process evaluation, and refinement of an oral health community participatory project in Mount Pleasant, an inner-city Latino neighborhood of Washington, DC. The main goal was to explore the feasibility of implementing such a project.